Roadside worker detection and alert system using RFID - Norizan, S.N.I.B. (Asian Research Publishing Network, 2015)
The project proposes a prototype system to alert drivers of the existence of roadside workers in order to reduce road accident rate involving roadside workers. High fatality rate involving roadside workers can be reduced by pre-alerting the drivers at a safe distance. A distance alert system is proposed to meet the need of alerting the drivers earlier to prevent accidents. Radio Frequency Identification (RFID) technology is used to indicate the existence of roadside workers and alert the drivers. The prototype system had been developed to clearly show and demonstrate the idea of giving alert to the driver on the existence of the roadside worker. In order for the prototype system to work effectively, RFID reader has to detect RFID tag and transfer the signal to a buzzer. The buzzer informs to the driver of the existence of nearby roadside workers for them to stay alert, and slows down, or change path if necessary. The objectives of this project are to study the implementation of Radio Frequency Identification (RFID) as a simulator in detecting workers at the roadside of a highway and to develop a prototype system that can notify the driver on the presence of the worker at the highway. The significance this project; is to save lives by providing sufficient reaction time for drivers to safely avoid roadside workers.